Populasi Ascaridia galli Dalam Usus Halus Ayam Yang Diberikan Kombinasi Ekskretori/Sekretori L3 dan Imunoglobulin Yolk - Darmawi Darmawi; Ummu Balqis; Risa Tiuria (Jurnal Agripet, 2011)
Ascaridia galli populations in intestine of chickens treated with combination of excretory/secretory L3 and immunoglobulin yolkABSTRACT. The purpose of the present study was to determine the presence of worm populations in intestine of chickens vaccinated and combined with egg yolk to experimental Ascaridia galli infection. Amount of 18 head chickens were devided into six groups (A F). Group A, the chickens were not vaccinated. Group B, the chickens were vaccinated with excretory/secretory of A. galli L3. Group C, the chickens were vaccinated with excretory/secretory of A. galli L3, challenged with dose 1000 L2, and treated ten times with 0,875 mg egg yolk with an interval of one day intra orally. Group D, the chickens were vaccinated with excretory/secretory of A. galli L3 and challenged with dose 1000 L2. Group E, the chickens were challenged with dose 1000 L2 and treated ten times with 0,875 mg egg yolk with an interval of one day intra orally. Group E, the chickens were challenged with dose 1000 L2. Intestinal worm burdens of infected groups were recorded. The result showed that excretory/secretory of A. galli L3 combined with egg yolk decreased significantly A. galli survival in intestine of laying hens. Vaccinations were positively correlated with worm burden at 12 weeks after chalanged. The results suggest that A. galli L3 excretory/secretory product contain potential antigen and that antibody-mediated mechanisms contribute to immune protection.